Unidad hospitalaria materno infantil: Una experiencia sensorial (2022)
Early childhood is a fundamental stage in the growth and development of human beings, in which important maturation processes, skills and abilities are established. Currently departments such as Choco, known for its cultural and natural biodiversity, are also the epicenter of diseases, and in addition to abandonment, presenting high indicators of unsatisfied basic needs and the highest neonatal, perinatal and infant mortality rates at the national level. Therefore, it is important to work on strategies that promote health and prevent diseases.